Association of robust nitrogen removal with spatiotemporal nitrifying bacterial community dynamics in a new bioreactor for treatment of simulated livestock wastewater with high ammonia content. Issue 2 (24th October 2018) - Zhang, Yimin; Kong, Ming; Hua, Ming; Wang, Longmian; Zhou, Mengyue; Peng, Fuquan; Qiu, Haoyu; Han, Wei; Gao, Yuexiang; Chao, Jianying; Xu, Bin; Yang, Fei; et al.
Abstract: BACKGROUND: Different types of nitrogen‐containing wastewater have been treated with dewatered alum sludge (DAS) or neutralized used acid (NUA) or with a combined DAS–NUA biofilter. The connections between the spatiotemporal structures of ammonia‐oxidizing bacteria (AOB) and nitrite‐oxidizing bacteria (NOB) and the nitrogen removal performance of DAS–NUA biofilter have not been fully clarified. To address this issue, AOB and NOB genetic characteristics response to nitrogen conversions in a laboratory‐scale DAS–NUA biofilter were investigated. RESULTS: The spatiotemporal distribution of the AOB in DAS was heterogeneous in the bioreactor. The trends observed in its structure were a function of depth along the flowpaths and time. However, AOB in NUA and NOB in both substrates were time and space independent. The spatial and temporal behavior of nitrifying bacteria mainly depended on the pH, followed by dissolved oxygen. The Shannon indexes of AOB and NOB and the relative abundances of Nitrosomonas and Nitrobacter had significantly negative relationships with NH + 4 –N and total nitrogen concentrations in effluents. CONCLUSIONS: The Shannon indexes of AOB and NOB and the relative abundances of Nitrosomonas and Nitrobacter were the key indicators of nitrogen removal and have implications for effective nitrogen attenuation strategies. © 2018 Society of Chemical Industry